Clinicopathologic Features of Anal and Perianal Squamous Cell Carcinomas and Their Relationship to Human Papillomavirus. (June 2019) - Ju, Jennifer Y.; Stelow, Edward B.
Abstract : Anal squamous cell carcinomas (ASCCs) frequently harbor human papillomavirus (HPV), most commonly high-risk (HR-) HPV type 16. While p16 immunohistochemistry (IHC) is typically used as a surrogate for HR-HPV status in the oropharynx and cervix, its overexpression can also occur as a result of oncogenic stress and sometimes prove nonspecific. There have been recent investigations into the use of HPV RNA in situ hybridization (RISH) assays as an alternative method, which have shown robust results for squamous cell carcinomas of the oropharynx and cervix. Our study evaluated HPV RISH and p16 IHC in 50 ASCCs, as well as the clinicopathologic features of ASCC relative to HPV status. We found that HPV RISH and p16 IHC were closely in agreement with 96% concordance. Using the 2 methodologies, 78% of ASCCs were HR-HPV positive, 10% were low-risk HPV positive, and 12% were HPV-negative. None of our cases showed co-infection across HR-HPV and low-risk HPV. ASCCs that were not related to HR-HPV were more likely to have a typical keratinizing morphology ( P =0.05) and more likely to involve the perianal area ( P =0.006). HPV-negative cases were particularly aggressive with high rates of metastases and patient death within 2 years of diagnosis. Overall, HPV RISH appears to be a reliable methodology for testing, and HPV status may have implications for prognostication of ASCCs.